EFFECTS OF 2,4-DICHLOROPHENOXYACETIC ACID (2,4-D) ON OPEN-FIELD BEHAVIOR AND NEUROCHEMICAL PARAMETERS OF RATS - Oliveira, G. H.; Palermoneto, J. (Munksgaard Int Publ Ltd, 1993)
The effects of the herbicide 2,4-dichlorophenoxyacetic acid (2,4-D) on the central nervous system (CNS) were studied in rats. Behavioural and neurochemical studies were performed. Results show that acute and oral administration of dimethylamine 2,4-D was able to decrease locomotion and rearing frequencies and to increase immobility duration of rats observed in an open-field test. Treatment of rats with p-chlorophenylalanine (PCPA) was unable to change rat's open-field behaviour; 5-hydroxytryptophan (5-HTP) administration not only increased locomotion and rearing frequences but also decreased immobility duration. Pretreatment of the rats with PCPA and 5-HTP decreased and increased dimethylamine 2,4-D effects, respectively. The herbicide was not able to change the striatal levels of dopamine and homovanilic acid but decreased the striatal levels of serotonin (5-HT), as observed for the doses of 100 and 200 mg/kg and increased those of 5-hydroxyindoleacetic acid (5-HIAA) as measured after the 200 mg/kg dose treatment. When the levels of serotonin and 5-HIAA were measured at the brain stem level, only those of 5-HIAA were modified, being increased by diethylamine 2,4-D (60; 100 and 200 mg/kg); this increment on 5-HIAA levels was observed even 1 hr after pesticide administration. Further analysis showed that 2,4-D concentrations chromatographycally detected both in serum and brain of the intoxicated animals were dose-dependent, being found as early as 1 hr after the smaller dose of the herbicide used (10 mg/kg). The results suggest that diethylamine 2,4-D modify 5-HT functional activity within the CNS. Thus, the effects of the herbicide on open-field behaviour of rats could be attributed to a direct or indirect pesticide action on serotoninergic systems.